Learning to love: Pastoral care as mission at church-based, intercultural initiatives - Holdsworth, Sue (Ecclesial Futures, 2023)
This article speaks to the relationship between social action and mission. It argues that mission at church-based, intercultural initiatives is better understood and enabled when principles and practices of pastoral care are applied. A study of four, church-based intercultural initiatives in Melbourne demonstrated that the development of intercultural pastoral care practices offers a way to understand mission that is relevant for local-church-based community initiatives. Pastoral care and mission have a confused relationship in the literature and are brought into conversation with these four case studies, demonstrating that pastoral theology has insights to offer mission. In particular, this article explores themes of compassion and empathy, formation for hospitality, and the need for deeper spiritual formation in local, church-based, intercultural community initiatives. This is an important understanding at a time when many Western Christians seem at a loss to know how to effectively engage with others in a rapidly changing and often indifferent society. It is suggested that mission is framed as pastoral care at similar, church-based initiatives. Pastoral formational practices of reflective practice, spiritual engagement and supervision are recommended for all engaged in church-based, intercultural mission and this has broader relevance to all engaged in mission.